Interleukin-1β Expression Is Required for Lysophosphatidic Acid-Induced Lymphangiogenesis in Human Umbilical Vein Endothelial Cells - Chih-Hsin Lin; JenHer Lu; Hsinyu Lee (International Journal of Inflammation)
Lysophosphatidic acid (LPA) is a lipid mediator which binds to G-protein-coupled receptors and regulates various cellular responses, including inflammation of endothelial cells. Interleukin- (IL-) 1β, a proinflammatory cytokine, is elevated upon LPA treatment in human umbilical vein endothelial cells (HUVECs). Previous studies indicated that LPA upregulates vascular endothelial growth factor- (VEGF-) C and lymphatic marker expressions in HUVECs. However, the relationships between LPA-induced VEGF-C and IL-1β expressions are not clear. In this paper, we demonstrated that, in the presence of AF12198, an inhibitor of the IL-1 receptor abolished LPA-induced VEGF-C and lymphatic marker expressions in HUVECs. Furthermore, LPA-induced in vitro tube formation of HUVECs was also suppressed by pretreatment with AF12198. Our results suggest that LPA-stimulated lymphangiogenesis in HUVECs is mediated through IL-1β-induced VEGF-C expression.